2009
DOI: 10.1111/j.1469-8137.2008.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulation of leaf colour in red 35S:PAP1 Arabidopsis thaliana

Abstract: Summary• High-temperature, low-light (HTLL) treatment of 35S:PAP1 Arabidopsis thaliana over-expressing the PAP1 (Production of Anthocyanin Pigment 1) gene results in reversible reduction of red colouration, suggesting the action of additional anthocyanin regulators. High-performance liquid chromatography (HPLC), liquid chromatography mass spectrometry (LCMS) and Affimetrix ® -based microarrays were used to measure changes in anthocyanin, flavonoids, and gene expression in response to HTLL.• HTLL treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
194
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(204 citation statements)
references
References 54 publications
9
194
0
1
Order By: Relevance
“…Upon JA treatment or JA biosynthesis stimulated by diverse developmental and environmental signals, the JA signal induces degradation of JAZ proteins through the SCF COI1 -26S proteasome pathway (Chini et al, 2007;Thines et al, 2007;; the WD-repeat/bHLH/MYB complexes are then released to activate their respective downstream transcriptional cascades, leading to anthocyanin biosynthesis and trichome formation. Many other signals, including environmental signals (cold, high light, and insect attack) and endogenous signals (cytokinins and gibberellin), were shown to regulate anthocyanin accumulation or trichome formation (Deikman and Hammer, 1995;Gan et al, 2007;Cominelli et al, 2008;Loreti et al, 2008;Rowan et al, 2009;Yoshida et al, 2009;Yu et al, 2010). These signals may influence anthocyanin accumulation and trichome initiation also through directly or indirectly regulating WD-repeat/bHLH/MYB complexes by virtue of bHLH and R2R3 MYB components as well as the WD-repeat protein TTG1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon JA treatment or JA biosynthesis stimulated by diverse developmental and environmental signals, the JA signal induces degradation of JAZ proteins through the SCF COI1 -26S proteasome pathway (Chini et al, 2007;Thines et al, 2007;; the WD-repeat/bHLH/MYB complexes are then released to activate their respective downstream transcriptional cascades, leading to anthocyanin biosynthesis and trichome formation. Many other signals, including environmental signals (cold, high light, and insect attack) and endogenous signals (cytokinins and gibberellin), were shown to regulate anthocyanin accumulation or trichome formation (Deikman and Hammer, 1995;Gan et al, 2007;Cominelli et al, 2008;Loreti et al, 2008;Rowan et al, 2009;Yoshida et al, 2009;Yu et al, 2010). These signals may influence anthocyanin accumulation and trichome initiation also through directly or indirectly regulating WD-repeat/bHLH/MYB complexes by virtue of bHLH and R2R3 MYB components as well as the WD-repeat protein TTG1.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis thaliana, the WD-repeat protein Transparent Testa Glabra1 (TTG1) (Walker et al, 1999) recruits basic-helixloop-helix (bHLH) transcription factors (Toledo-Ortiz et al, 2003), such as Glabra3 (GL3) (Payne et al, 2000), Transparent Testa8 (TT8) (Nesi et al, 2000;Baudry et al, 2006), or Enhancer of Glabra3 (EGL3) , and R2R3 MYB transcriptional factors (MYB75, MYB90, MYB113, or MYB114) (Borevitz et al, 2000;Stracke et al, 2001;Zimmermann et al, 2004;Stracke et al, 2007;Allan et al, 2008;Gonzalez et al, 2008;Rowan et al, 2009) to form the WD-repeat/bHLH/MYB complex, which mediates anthocyanin biosynthesis mainly by upregulating the expression of late anthocyanin biosynthetic genes, including NADPH-dependent dihydroflavonol reductase (DFR), leucoanthocyanidin dioxygenase (LDOX), and UDP-Glc:flavonoid 3-Oglucosyltransferase (UF3GT) (Dooner et al, 1991;Kubasek et al, 1992;Shirley et al, 1995;Gonzalez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, petunia, maize, A. majus, and fruit trees, it has been shown that MYB TFs, together with basic helix-loop-helix TFs and WD-40 repeat proteins, regulate anthocyanin biosynthesis and therefore contribute to the red coloration of various organs including the leaves, flowers, and fruits (Mol et al, 1998;Allan et al, 2008). Generally, light induces the expression of anthocyanin-associated MYB genes, and therefore favors red pigment accumulation in plant organs (Mol et al, 1998;Allan et al, 2008;Gonzalez, 2009;Rowan et al, 2009). In apple, the fruit peel does not develop a red color without light, but it rapidly initiates coloration upon exposure to sunlight in a process that is regulated by MdMYB1 and its alleles (Takos et al, 2006;Ban et al, 2007;Allan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, anthocyanin accumulation only occurs in the light (Maier et al, 2013) and the levels of anthocyanin accumulation are light intensity dependent (Rowan et al, 2009;Shi and Xie, 2010). In this study, we maintained Arabidopsis seedlings under weak light of 40 mmol m 22 s 21 (hereafter called low light), a control light intensity at which wild-type plants accumulate very low levels of anthocyanins (Shi and Xie, 2010;Maier and Hoecker, 2015) (Figures 2A and 2B).…”
Section: Mpk4 Is Involved In High Light-induced Anthocyanin Accumulationmentioning
confidence: 99%